An Intelligent AntNet-Based Algorithm for Load Balancing in Grid Computing (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Computational grids have a huge number of diverse and scattered resources that are used in handling complex problems. A decent load balancing methodology is needed to utilize grid resource by efficiently distributing tasks, for execution, on available computing nodes.Ant colony is a major and popular method for approximate optimization. It works by simulating the actual ant‟s demeanor in detecting the best path for the resources of food. This research paper employs ant colony optimization in proposing a load balancing technique for computational grids. The performance of the suggested technique is computed, evaluated and compared with that of a Random Distributed Load Balancing technique using simulation. The achieved results reveal that the suggested technique enhances the task average response time. It reveals also that the enhancement ratio progressively rises up as the system‟s load rises up till the load come to be mild where the best enhancement ratio is achieved. Immediately after that, the enhancement ratio declines steadily as the system‟s load rises up till the system becomes saturated.